Absence of CD4(+)CD25(+) regulatory T cells is associated with a loss of regulation leading to increased pathology in Helicobacter pylori-infected mice - RAGHAVAN, S (Blackwell Science Inc, 2003)
Helicobacter pylori induces symptomatic chronic gastritis in a subpopulation of infected individuals. The mechanism(s) determining the development and severity of pathology leading to symptoms are not fully understood. In a mouse model of H. pylori infection we analysed the influence of immunoregulatory CD4(+)CD25(+) T cells on H. pylori colonization and gastritis. Athymic C57BL/6 nu/nu mice were reconstituted with (a) lymph node (LN) cells (b) LN cells depleted of CD25(+) T cells (CD25(–) LN) or (c) not reconstituted at all. Mice were then infected orally with 3 × 10(8)H. pylori SS1 bacteria. At 2 and 6 weeks after the inoculation there was a significant (P < 0·001) reduction in H. pylori colonization in athymic mice transferred with CD25(–) LN cells compared to mice transferred with LN cells. Colonization was still reduced at 12 weeks after inoculation. Mice transferred with CD25(–) LN cells showed an earlier onset and increased severity of gastritis as compared to mice receiving LN cells. Splenic cells isolated from mice receiving CD25(–) LN cells produced the highest level of IFN-γ on stimulation with H. pylori antigens in vitro, had a higher H. pylori-specific DTH response and increased infiltration of CD4(+) T cells and macrophages in the gastric mucosa. Athymic mice not transferred with T cells had persistent high H. pylori colonization and displayed a normal gastric epithelium without inflammatory cells. In conclusion, CD4(+)CD25(+) cells reduce immunopathology in H. pylori infection, possibly by reducing the activation of IFN-γ producing CD4(+) T cells, even at the expense of a higher H. pylori load in the gastric mucosa.